Food Packaging - Luky Hartini (Balai Besar Kimia dan Kemasan, 1977)
A food package is a structure designed to contain a food product, The functions of a Package are basically to contain, carry and dispense. As timewent on, there were added other requirements such as to preserve, to measure, and later to communicate and to display. Several kinds of the modern packaging are glass container, cans, composite container, aerosol container and flexible packaging.